Analysis of second-order effects according to Eurocode 2 - Dushanovska, Sofija; Nakov, Darko; Markovski, Goran; Arangjelovski, Toni; Popovski, Denis (Macedonian Association of Structural Engineers (MASE), 2022)
The Eurocode, as the current design code in our country, allows designing objects according to contemporary standards but also opens a great number of research topics. The focus of this paper will be the two simplified methods that Eurocode 2 offers for the calculation of the second-order effects, which are particularly important when designing construction elements with great height or with large longitudinal forces. The second-order moments will be calculated for columns by varying a larger number of factors that, less or more, influence the final results. Thereby, the two simplified methods in Eurocode 2, method of nominal stiffness and method of nominal curvature, will be applied and compared. The main goal is to determine how the change of some factors, like: effective length, concrete class, cross-section, stiffness of the elements which is connected with the cracks, affects the second-order moments calculated with the two methods. These analysеs will be conducted in 6 key studies for isolated columns. The key studies will determine the actual influence that the second-order moments have. From the calculations made with the two methods different results for the moments are obtained, but to a certain value, the results are with an insignificant difference. The reason why the method of nominal stiffness and the method of nominal curvature give different results will be explained and the point at which they give approximate results will be determined. In the conclusions, everything that has been determined within the analyses will be highlighted. Given that Eurocode 2 leaves the opportunity to choose the method of analysis of the second-order effects up to the country’s National Annex, with the analyses made a contribution to that decision was made, with a conclusion which method is more appropriate for calculating the second-order effects.
Keywords: Eurocode 2; second-order effects, method of nominal stiffness, method of nominal curvature